The Effect Of Giving Ocimum sanctum L. Leaf Extract On Growth Of Bacteria Bacillus cereus - Evalentina Nababan; Hasruddin Hasruddin (JBIO: jurnal biosains (the journal of biosciences), 2015)
The aim of this research is to know the effect giving Ocimum sanctum L. leaf extract on growth of bacteria Bacillus cereus. This research has been done in microbiology laboratory FMIPA UNIMED in March 2015. The design of experiment of this research is Random Sampling Non Factorial with six concentrations Ko = 0%, K1 = 2%, K2 = 4%, K3 = 6%, K4 = 8% dan K5 = 10%. The parameter observed of bacteria Bacillus cereus for 48 hours by calculating blocked zone diameter with incubation period 1 x 24 hours and 2 x 24 hours. The result of the research data shows that different concentration of Ocimum sanctum L. effect on the blocked zone diameter of Bacillus cereus growth. The largest blocked zone diameter is 12,9 mm which is produced by 10% concentration of Ocimum sanctum L. leaf extract with incubation time 2 x 24 hours and the smallest blocked zone diameter is 4,7 mm which is produced by 2% concentration of Ocimum sanctum L. leaf extract with incubation time 2 x 24 hours.   Key words: Etanol, Ocimum sanctum L. leaf, Bacillus cereus.